Foreign direct investment : potential and economic impact on Azerbaijan economy - Nazarov, Nijat; Šíma, Ondřej; Pour, Jiří; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2023)
This master's thesis examines the potential of foreign direct investment (FDI) in Azerbaijan and evaluates its impact on the country's economy. Azerbaijan has been actively pursuing foreign investment to diversify its economy, promote industrial development, and reduce its dependence on oil and gas exports. The study aims to answer research questions related to the current state of FDI, the factors contributing to the success or failure of FDI initiatives, the economic impact of FDI, and the potential benefits and challenges of FDI for Azerbaijan's economy. The research employs a qualitative approach based on a literature review of academic journals, reports, and statistical databases to analyze and synthesize existing literature. The study provides insights into the factors that influence FDI inflows to Azerbaijan and the channels through which FDI affects economic growth and development.
Vedoucí práce: Ondřej Šíma
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses